Technical writing - Cornista, Aleli N. (Dagupan City : SLA Publishing House, 2000)
Technical writing is designed to be a comprehensive, thoroughly practical reference guide for college students taking up technological courses such as engineering, architecture, geology, and other related studies.
1. Technical writing: an introduction -- 2. Technical wiring style -- 3. Writing paragraphs -- 4. The technical composition -- 5. Graphic aids -- 6. Writing the library research report.
Keywords: TECHNICAL WRITING